Discordant effects of rosiglitazone on novel inflammatory biomarkers - Gada, Elan; Owens, Andrew W.; Gore, M. Odette; See, Raphael; Abdullah, Shuaib M.; Ayers, Colby R.; Rohatgi, Anand; Khera, Amit; de Lemos, James A.; McGuire, Darren K. (The American heart journal, 2013)
Although rosiglitazone favorably affects myriad intermediate markers of atherosclerosis, it appears to increase myocardial infarction (MI) risk. We analyzed the effects of rosiglitazone on a panel of 8 novel circulating biomarkers, 4 of which are independently associated with atherosclerosis: lymphotoxin β receptor, peptidoglycan recognition protein 1, chemokine ligand 23, and soluble receptor for advanced glycation end products (sRAGE) as well as on high-sensitivity C-reactive protein (hs-CRP). Blood samples were analyzed at baseline and after 6 months of study treatment from subjects with type 2 diabetes with or at high risk for coronary artery disease in a randomized trial comparing rosiglitazone versus placebo. Data from 111 subjects (rosiglitazone 55, placebo 56) were analyzed. Mean age was 56 years, 41% were women, and 66% were nonwhite. Compared with baseline values, rosiglitazone adversely affected levels of lymphotoxin β receptor (1.7 vs 2.4 ng/mL, P = .002), peptidoglycan recognition protein 1 (29.0 vs 30.1 ng/mL, P = .01), and chemokine ligand 23 (0.76 vs 0.84 ng/mL, P = .02) and favorably affected levels of sRAGE (inversely associated with atherosclerosis, 1.1 vs 1.4 ng/mL, P = .003) and hs-CRP (0.42 vs 0.31 ng/mL, P = .02); no changes were observed with rosiglitazone in the other biomarkers. In the placebo group, change was observed only for sRAGE (1.0 vs 1.1 ng/mL, P = .046). Rosiglitazone adversely affected 3 novel biomarkers and favorably affected a fourth previously associated with atherosclerosis while improving hs-CRP, as has previously been shown. Whether these complex effects on circulating inflammatory biomarkers contribute to the signal of increased MI risk with rosiglitazone and whether pioglitazone has similar effects warrant further investigation.